DAYA HAMBAT GETAH LIDAH BUAYA (ALOE VERA) TERHADAP PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTANS - Ayu D P; Sadimin Sadimin; Sariyem Sariyem; Hermien Nugraheni (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEInhibitory effect of aloe vera mucilage to Streptococcus mutans growthABSTRACT Aloe vera contains various components of compounds, one of which is aloin and saponin (5.9%), which has an antibacterial effect so as to inhibit the growth of Streptococcus mutans bacteria. Streptococcus mutans is known as a bacterium that can cause dental caries. The purpose of this study was to determine the inhibition of aloe sap to the bacteria Streptococcus mutans.This study uses a quasi-experimental methods. Research subjects used was Streptococcus mutans bacteria. The design of this study to make aloe vera sap solution with a concentration of 50%, 75% and 100%, then make a suspension of bacteria Streptococcus mutans. After the treatment, carried incubation for 1 X 24 hours in an incubator, the results do observation and measurement (post-test) of the diameter of the inhibition area Streptococcus mutans bacteria growth by using a ruler (mm). Data were analyzed using quantitative descriptive analysis method.Based on the research results, the sap of aloe vera with a concentration of 50% has to Streptococcus mutans inhibition of 10.15mm, the concentration of 75% amounting to 10.26mm, the concentration of 100% inhibition against Streptococcus mutans bacteria by 20.7mm. So it can be concluded that there is a difference in the concentration of aloe vera sap as inhibiting the growth of bacteria Streptococcus mutans that the higher the concentration used, the greater the inhibition of the growth of Streptococcus mutans bacteria. Keywords : AloeVera, Streptococcus mutans.